INVENTORY PENGADAAN BARANG K3 BERBASIS WEBSITE (STUDI KASUS: PT WIJAYA KARYA BETON) - Hidayat , Tirana Praticia; Sopiandi, ii (Universitas Majalengka, 2025)
This research aims to develop a website-based inventory system for Occupational Health and Safety (K3) equipment procurement at PT Wijaya Karya Beton Majalengka. The study was conducted because the manual system still used by the company causes various problems such as inefficiency, recording errors, lack of data transparency, and difficulties in tracking and reporting. The research method used is Research and Development (R&D) with a RAD (Rapid Application Development) approach consisting of four stages: Requirements Planning, Design User, Development, and Testing & Implementation. Data collection techniques include interviews with factory managers, field observations, and literature studies. The system was developed using web technology with Next.js as the framework, PHP as the server-side programming language, and MySQL as the database. System design uses UML (Unified Modeling Language) consisting of use case diagrams, sequence diagrams, class diagrams, and activity diagrams. System testing was carried out using the Black Box Testing method with feature testing techniques. The research results show that the system was successfully developed with main features in the form of goods management (add, update, delete), management of goods usage and return, as well as inventory reporting. The system has proven to improve procurement process efficiency, minimize administrative errors, increase data transparency and accuracy, and facilitate inventory tracking and reporting of K3 equipment. Implementation of this system is expected to support better K3 implementation and create a safer and healthier work environment